The association of Crohn's disease, Celiac disease and selective Ig A deficiency - Tankova, Ludmila; Gerova, Vanya; Getsov, Plamen; Penkov, Nikolay; Taneva, Gergana; Terziev, Ivan; Nakov, Radislav (International journal of celiac disease, 2016)
Concomitant occurrence of celiac disease (CeD) and Crohn's disease (CD) is rare and has been reported in several case reports and series. We report a case of a 63-year-old man with proximal CD, CeD and selective immunoglobulin (Ig) A deficiency (SIgAD). The patient was admitted in our Clinic for evaluation of epigastric pain, nausea, vomiting and weight loss (up to 7 kg) appeared in the last 3 months. The imaging findings from abdominal ultrasound and CT enterography raised suspicion of a lymphoproliferative disease of the jejunum. To exclude the development of lymphoma based on long standing untreated atypical CeD, upper endoscopy with biopsies and serological tests were conducted, showing and subtotal villous atrophy and elevated levels of IgG tissue transglutaminase tTG. Histopathology documented CD (A3,L4,B2 according to Montreal's classification).
Keywords: Celiac Disease; lidé středního věku; Crohnova nemoc; komorbidita; lidé; Crohn Disease; mužské pohlaví; IgA Deficiency; Comorbidity; Male; Middle Aged; celiakie; deficience IgA; Humans